Targeted ultraviolet B phototherapy: definition, clinical indications and limitations. (1st January 2015) - Alshiyab, D.; Edwards, C.; Chin, M. F.; Anstey, A. V.
Summary: Targeted ultraviolet B (UVB) phototherapy is defined as UVB radiation applied only to clinically diseased skin, with sparing of adjacent normal skin, unlike conventional phototherapy, which involves irradiation of both diseased and normal skin. Targeted UVB radiation is a relatively new concept, which is now widely available because of advances in technology. Devices developed for targeted UVB phototherapy of the skin include the monochromatic excimer laser and lamp, both of which are now used by dermatologists in developed and developing countries. The aim of this review is to collate data from research studies on targeted phototherapy and to provide a concise description of currently available devices, their clinical indications and therapeutic efficacy. Additionally, potential adverse effects are summarized, and the limitations of these novel devices are highlighted. Abstract : Click here for the corresponding questions to this CME article.